The Relationship between The Use of Albumin and The Management of Nephrotic Syndrome with Hypovolemia : A Systematic Review - Aswan Suwandi; Nanda Dayana Harahap (The International Journal of Medical Science and Health Research, 2026)
Introduction: Nephrotic syndrome (NS) with hypovolemia presents a clinical paradox: significant peripheral edema coexists with intravascular volume depletion. Intravenous albumin is commonly used to manage this condition, yet its efficacy and safety remain debated. This systematic review evaluates the relationship between albumin use and the management of NS with hypovolemia. Methods: A systematic review was conducted screening abstracts from multiple databases. Studies were included if they involved human participants with NS and hypovolemia, evaluated human albumin administration (any concentration or dose), and reported outcomes related to volume status, renal function, or clinical improvement. Data extraction focused on patient characteristics, albumin intervention details, concurrent treatments, volume management outcomes, renal function effects, volume status assessment methods, and safety outcomes. Results: From 80 included sources, the evidence base is remarkably sparse. Two Cochrane reviews each identified only a single eligible RCT (Dharmaraj 2009, n=26). The most consistent finding is a transient increase in urine output and weight loss within the first several hours of albumin treatment (Kitsios et al., 2014; Lee et al., 2021). Meta-analyses show a pooled standardized mean difference of 0.85 (95% CI 0.33–1.38) for urine excretion favoring furosemide plus albumin (Hedin et al., 2022). However, diuretic benefits peak at 6–8 hours and are not sustained at 24 hours (Nawaz & Zafar, 2025). Sequential administration (albumin then furosemide) produces significantly greater weight loss than simultaneous co-infusion (Tadayoni et al., 2025). In congenital nephrotic syndrome (CNS), aggressive daily albumin use yields ~90% survival, comparable to conservative management (Bockenhauer & Boyer, 2024). No significant differences were found between 5% versus 20% albumin (Garg et al., 2020) or between albumin versus fresh frozen plasma (Singh et al., 2021). Safety data show rare but notable risks including hypertension and volume overload (Ellis, 2016; Moiseev et al., 2024). Discussion: The central finding reveals a paradox: albumin has strong physiological plausibility and produces measurable short-term improvements, yet randomized trial evidence is of very low certainty and effects are transient. The underfill-versus-overfill distinction is the critical determinant of albumin utility (Ellis, 2016; Jethwani & Krishnan, 2021). In underfill patients (FENa <0.2%, urinary K+/(K++Na+) >60%, serum albumin ≤2 g/dL), albumin may benefit acute management. In overfill patients, albumin may cause harm. The transience of effect is mechanistically explained by rapid urinary loss of infused albumin due to glomerular permeability (Bockenhauer & Boyer, 2024). For CNS, the debate between aggressive versus conservative management remains unresolved by RCTs, with retrospective data suggesting comparable outcomes (Boyer & Bérody, 2020; Dufek et al., 2018). In resource-limited settings, fresh frozen plasma, whole blood, or mannitol may serve as alternatives (Singh et al., 2021; Okoronkwo et al., 2018; Huque et al., 2014). Conclusion: Albumin provides transient diuretic benefit in select NS patients with confirmed hypovolemia (underfill physiology) but should be reserved for acute inpatient management of severe or diuretic-resistant edema. Routine outpatient or ongoing albumin therapy is not supported by current evidence. Future adequately powered RCTs stratifying by volume status are urgently needed.